Can Government Expenditure and Investment Drive Poverty Alleviation in Aceh Through Economic Growth? - Inayati, Inayati; Jamal, Abd.; Nasir, Muhammad (Indonesia Academia Research Society, 2024)
Poverty continues to be a significant challenge in economic development, attracting widespread attention globally. In response, various initiatives are being implemented to reduce poverty. This study explores the indirect effects of investment and government expenditure on poverty alleviation through economic growth in Aceh Province. Utilizing quantitative methods, including path analysis and multiple panel regression models, and drawing on data from 23 districts and cities in Aceh, the findings reveal that both investment and government expenditure have direct, positive, and statistically significant effects on economic growth. However, these variables do not have a direct impact on poverty levels. Specifically, government expenditure is negatively and significantly correlated with poverty, while investment shows a negative but statistically insignificant relationship. Economic growth itself also has a positive, yet statistically insignificant, relationship with poverty. Additionally, the analysis shows that economic growth does not mediate the effect of investment and government expenditure on poverty in Aceh. These results highlight that achieving high growth rates and large investment volumes alone is insufficient. It is essential to focus on the quality of growth, emphasizing the creation of a multiplier effect, fostering inclusive investment, improving infrastructure, and investing in human capital. Such efforts can ensure that economic growth effectively contributes to poverty reduction.